Study of the inhomogeneity of critical current under in-situ tensile stress for YBCO tape. (5th February 2018) - Zhu, Y P; Chen, W; Zhang, H Y; Liu, L Y; Pan, X F; Yang, X S; Zhao, Y
Abstract: A Hall sensor system was used to measure the local critical current of YBCO tape with high spatial resolution under in-situ tensile stress. The hot spot generation and minimum quench energy of YBCO tape, which depended on the local critical current, was calculated through the thermoelectric coupling model. With the increase in tensile stress, the cracks which have different dimensions and critical current degradation arose more frequently and lowered the thermal stability of the YBCO tape.